Las perlas de Rosa (1914) de Aurora Cáceres: una bella muerte. Imaginarios estético-ideológicos modernistas de entre siglos en clave femenina - Elena Grau-Lleveria (Les Cahiers ALHIM)
Within the modernist production, Las perlas de Rosa (1914), by Aurora Cáceres, constitutes an exceptional text because it presents the existential crisis of a woman in which the masculine modernist languages are put into play, contaminating them with a discourse of Christian forgiveness and redemption that, in turn, alter the hegemonic feminine Catholic ideology of the time. The lines of critical analysis that I propose in this article address the configuration of the novel's aesthetic-ideological languages and its narrative structure. This allows me to analyze the life and the vital crisis of the protagonist as a staging of the political struggle that Cáceres developed in this text to propose an ideology of representation of femininity different from those proposed by the modernists but within a modernist aesthetic languages.